In-depth comparative analysis of Tritrichomonas foetus transcriptomics reveals novel genes linked with adaptation to feline host - Alonso, Andrés Mariano (2022)
Tritrichomonas foetus is a flagellated parasite able to infect cattle, cats, and pigs. Despite its prevalence, feline tritrichomonosis has received markedly less attention than venereal infection, and little information about the molecular mechanisms that participate in feline host infection is available. Through a bioinformatics approach, we integrated public transcriptomic data for three T. foetus isolates and explored the differences at transcript level with a focus on pathogenesis and adaptation processes, particularly for the feline isolate. Our analysis revealed higher abundance levels of predicted virulence factors, such as proteases and surface antigens. Additionally, by a comparative and expression analysis of T. foetus genes, we proposed putative virulence factors that could be involved in feline infection. Finally, we identified a great proportion of predicted transcription factors of the MYB protein family and, by a promoter analysis, we revealed that MYB-related proteins could participate in the regulation of gene transcription in T. foetus. In conclusion, this integrated approach is a valuable resource for future studies of host–pathogen interactions and identifying new gene targets for improved feline tritrichomonosis diagnosis and treatment.